2011
DOI: 10.1007/s12155-011-9153-3
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Internode Composition During Crop Development

Abstract: Sugarcane sugar and bagasse can be utilized for the production of ethanol or other biofuels. A better understanding of the changes in composition with development along the stalk and with crop development will maximize the usage of sugarcane for this purpose. Two experiments were designed to elucidate internode composition changes during the growing season. In experiment 1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 26 publications
11
25
2
4
Order By: Relevance
“…Cellulose, hemicellulose, and lignin are critical factors affecting forage digestibility and livestock industry. In agreement with the previous studies (Chen et al, 2002; Jung and Casler, 2006; Lingle and Thomson, 2012; Rancour et al, 2012; Zhang et al, 2013), a continuous increase in lignin accumulation was observed in internode 2 from the E2 to E4 stage and the successive ones along the culm at the R1 stage as well. Moreover, an impressive shifting of lignin composition was observed in internodes at late stages in sheepgrass, implying that S lignin units may play an important role in cell wall strengthen and mechanical support of culms.…”
Section: Discussionsupporting
confidence: 92%
“…Cellulose, hemicellulose, and lignin are critical factors affecting forage digestibility and livestock industry. In agreement with the previous studies (Chen et al, 2002; Jung and Casler, 2006; Lingle and Thomson, 2012; Rancour et al, 2012; Zhang et al, 2013), a continuous increase in lignin accumulation was observed in internode 2 from the E2 to E4 stage and the successive ones along the culm at the R1 stage as well. Moreover, an impressive shifting of lignin composition was observed in internodes at late stages in sheepgrass, implying that S lignin units may play an important role in cell wall strengthen and mechanical support of culms.…”
Section: Discussionsupporting
confidence: 92%
“…The lignin content measured with the Klason method showed a continuous increase until the fifth internode for IACSP04-683 and until the sixth internode for IACSP04-529, after which much less variation was observed during later stages of stem development. This pattern of lignification is in agreement with previous reports (Lingle and Thomson, 2012). A similar developmental pattern of lignin deposition was observed in switchgrass (Panicum virgatum), a C4 perennial forage grass that has been selected for development as a biofuel crop in North America, and for which a fast increase in lignin content was observed during the progressive elongation stage (Shen et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the second experiment are similar to the maize results of Jung and Casler (2006), who suggest that young maize tissue is comprised of a higher percentage of lignified protoxylem vessels than more mature tissue, that initially results in a high lignin content in very young tissue (Jung & Casler 2006). It is likely that the Section A tissue (from internodes 2 and 3) was in what is the second zone identified in the studies by Jung and Casler (Jung & Casler 2006) and Lingle and Thomson (Lingle & Thomson 2012). This is supported by the results of Bottcher et al (2013) who showed lower lignin levels in internode 2-4 of two sugarcane cultivars before reaching a relatively steady state lignin level for internodes 5 to 18.…”
Section: Discussionsupporting
confidence: 81%